Periclinal fold systems in thick-bedded mudstones: A case study of the Early Cretaceous Hekou Group, Lanzhou Basin, NW China. (August 2022) - Zhang, Jin; Ukar, Estibalitz; Qu, Junfeng; Zhang, Beihang; Zhao, Heng; Zhang, Yiping; Wang, Zhenyi
Abstract: A new type of structural association comprising periclinal folds is present in thick-bedded calcareous mudstones and siltstones of the Early Cretaceous Hekou Group in the Lanzhou Basin, NW China. The periclinal fold system consists of meso-scale, open anticlines and synclines with fold axial trends in two perpendicular orientations (NE-SW and NW-SE) and two sets of conjugate thrust faults that form intersections in the same two orientations. Folded and faulted layers of the periclinal fold system are not sedimentary bedding surfaces but sub-parallel curviplanar foliations formed by compaction of the original strata soon after deposition. Many folded curviplanar foliations connect with the unfolded, conjugate thrust faults, indicating that faulting was active during and/or soon after folding. The NE-SW and NW-SE-trending fold axes and fault planes indicate bilateral, subhorizontal contraction acting simultaneously during the formation of the periclinal fold system. In some cases, converging slickenlines on curviplanar foliation planes within anticline cores point to localized isotropic contraction probably caused by scaping fluids and increased hydrostatic pressure. Similarities with the better-known polygonal fault system include development in fine-grained sediments and layer boundness, whereas main differences are a dominance of contractional faults in the periclinal fold system versus extensional faults in the polygonal fault system and a higher consolidation of sediments needed for the development of the periclinal fold system. This study suggests that collision between the Lhasa and Qiangtang Blocks combined with oblique convergence and subsequent collision along the southeastern margin of the Eurasian plate following compaction-related volume loss of fine-grained sediments led to the formation of the periclinal fold system in the Hekou Group in the Late Cretaceous. Highlights: A type of structural association named as "Periclinal Fold System" is first reported. The Periclinal Fold System develops in thick-bedded mudstones and siltstones. Compaction fabrics are folded in the Periclinal Fold System, but not bedding planes. The Periclinal Fold System is formed in the constrictional setting.